The Relationship Between Knowledge And Teachers' Perception Of Smoke-Free Area (KTR) In Its Implementation In State Junior High School Of Sleman District - Nadia Amalia Puspitasari; Purwanta; Elsi Dwi Hapsari (Journal of Nursing Management Innovations, 2026)
Background: KTR is an area prohibited for smoking, promoting, making and/or selling cigarettes. The scope of KTR are locations with academic importance. Sleman Regency has KTR regulation under Sleman Regent's Regulation No 42, 2012. The KTR implementation in Public Junior High Schools (JHS) has not been effective, as depicted by non-smoking rates data which is only 86%. Field studies also showed that some teachers still smoke in schools. Aims and Scope of the Paper:  This research aimed to determine the relationship between knowledge and teachers' perception in KTR implementation in Sleman District Public JHS. Methods:  The method of this study is cross-sectional design with multistage random sampling involving 223 teachers from 11 Public JHS. Results:  Univariate data analysis used to determine the characteristics, knowledge level and perceptions of KTR implementation. Bivariate analysis used to determine the relationship between knowledge and perception. This study was conducted from April to May 2019. Based on total scores, 118 respondents (52.9%) had high knowledge about KTR and 147 respondents (65.9%) had good perceptions of KTR implementation. The chi-square analysis resulted in p=0.031 with r=0.149. Conclusion:  The majority of teachers have high knowledge and good perception of KTR. There is a positive correlation between knowledge and teachers' perceptions of KTR implementation in Sleman District Public JHS.